Prevalence of axis II comorbidities in bipolar disorder: relationship to mood state. (25th January 2018) - Post, Robert M; Leverich, Gabriele S; McElroy, Susan; Kupka, Ralph; Suppes, Trisha; Altshuler, Lori; Nolen, Willem; Frye, Mark; Keck, Paul; Grunze, Heinz; Hellemann, Gerhard
Abstract: Objectives: A high incidence of Axis II personality disorders is described in patients with bipolar disorder; however, their relationship to mood state remains uncertain. Methods: A total of 966 outpatients with bipolar disorder gave informed consent and filled out the Personality Disorder Questionnaire, 4th edition (PDQ4) and a questionnaire on demographics and course of illness prior to Bipolar Treatment Outcome Network entry at average age 41 years. Patients were rated at each visit for depression on the Inventory of Depressive Symptoms‐Clinician version (IDS‐C) and for mania on the Young Mania Rating Scale (YMRS). In a subgroup, the PDQ4 was retaken during periods of depression and euthymia. Results: Patients met criteria for most personality disorders at a much higher rate when they took the PDQ4 while depressed compared to while euthymic, and scores were significantly related to the severity of depression (IDS) and of mania (YMRS) assessed within 2 weeks of taking the PDQ. Even when euthymic, more than quarter to half of the patients met criteria for a cluster A, B or C personality disorder. Conclusions: A wide range of personality disorders occur in bipolar patients, but are highly dependent on filling out the form while depressed compared to while euthymic. How this relates to having a personality disorder assessed using a structured clinical interview remains to be tested. However, higher PDQ4 scores are related to an earlier age of onset of bipolar disorder and other factors portending a more difficult course of bipolar disorder, and the optimal treatment of these patients remains to be illuminated.